Comparative study between the visual outcome of phacoemulsification and small incision cataract surgery - Mohammed S Ahmed (Journal of Medicine in Scientific Research, 2021)
Introduction Cataract is still one of the most common causes of visual impairment worldwide. Phacoemulsification is the primary method for cataract surgery in developed countries. However, it is associated with high cost and small incision cataract surgery (SICS), which has become an alternative surgery for phacoemulsification, mostly in developing countries. Patients and methods This study was carried out aiming to compare the effectiveness [postoperative visual acuity (VA)] of phacoemulsification versus SICS. Four hundred and fifty cataract patients, allocated into two groups with no statistically significant differences in their basic characteristics, were included in the current study. Patients in the first group underwent phacoemulsification and those in the second group underwent SICS; patients were followed up for 28 days. Results This study revealed no statistically significant differences between the phacoemulsification and SICS groups in visual outcome or proportion of patients with normal vision at follow-up. Furthermore, no statistically significant differences were found between both methods in the incidence of intraoperative or postoperative complications. The effectiveness of phacoemulsification and SICS in improving VA was found to be similar. SICS should be considered for more frequent use in high-volume mass cataract surgery. Conclusion In conclusion, SICS has comparable effectiveness with phacoemulsification in improving VA and should be considered in developing countries and rural areas.